'Clothes (don't) make the man': Fashioning the phallus in Sabine Bernardi's Romeos. Issue 1 (27th February 2023) - Piontek, Thomas
German director Sabine Bernardi's Romeos presents a progressive and more complete view of transgender experience than a previous generation of films on the subject. Skilfully avoiding outdated tropes in her representation of the female-to-male (FTM) trans man Lukas's transition, the film instead places it in a cultural and sociopolitical context that shows him confronting 'cultural cisgenderism' and negotiating the medicalization of his 'condition' to obtain the mastectomy he wants. Romeos, however, does not posit surgical intervention as the central element in its protagonist's transition but shows how gender identity and expression are conceived internally, independently of the individual's embodiment. Thus, this article argues that the developing maleness and masculinity that Lukas exhibits demonstrates that there exists a significant difference between the penis and the phallus. Lukas is able to 'fashion the phallus' – what social psychologists have called a 'cultural genital' – with a combination of appearance (including his fashionable male attire), hormone therapy and a strict workout regime. Even though a male genital may not be present in a physical sense, the significance attributed to his cultural genital allows Lukas to express his psychic gender identity and to establish the trans man, in the words of one gender theorist, as 'attractive, appealing, and gendered while simultaneously presenting a gender at odds with sex, a sense of self not derived from the body'. Still the discrepancy between his gender identity and his embodiment at times causes considerable problems for Lukas, especially when his love interest, the cisgender Fabio, accidentally finds out that Lukas is trans and questions his physical genital. That Lukas nonetheless manages to establish himself as a desiring subject capable of establishing a romantic relationship with Fabio and consummating it by having sex with him bespeaks the power of self-definition and the significant role that the cultural genital plays in this process.